2011
DOI: 10.1002/dvdy.22573
|View full text |Cite
|
Sign up to set email alerts
|

mab21l2 transgenics reveal novel expression patterns of mab21l1 and mab21l2, and conserved promoter regulation without sequence conservation

Abstract: mab21l1 and mab21l2 paralogs have widespread and dynamic expression patterns during vertebrate development. Both genes are expressed in the developing eye, midbrain, neural tube, and branchial arches. Our goal was to identify promoter regions with activity in mab21l2 expression domains. Assays of mab21l2 promoter-EGFP constructs in zebrafish embryos confirm that constructs containing 7.2 or 4.9 kb of mab21l2 promoter region are sufficient to drive expression in known (e.g., tectum, branchial arches) and unexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 40 publications
(19 reference statements)
1
23
0
Order By: Relevance
“…Previously published reports of lens expression in animal models are somewhat inconsistent: four studies reported lack of lens expression for Mab21l2/mab21l2 (with many showing the presence of lens expression for its close homolog, Mab21l1/ mab21l1 ) [41,4345] while three other manuscripts noted Mab21l2/mab21l2 transcripts in the developing lens [33,46,47], which is consistent with the results of our study. In zebrafish, morpholino-mediated knockdown of mab21l2 resulted in microphthalmia and incomplete retinal development including discontinuous inner and outer plexiform layers [47].…”
Section: Discussionsupporting
confidence: 86%
“…Previously published reports of lens expression in animal models are somewhat inconsistent: four studies reported lack of lens expression for Mab21l2/mab21l2 (with many showing the presence of lens expression for its close homolog, Mab21l1/ mab21l1 ) [41,4345] while three other manuscripts noted Mab21l2/mab21l2 transcripts in the developing lens [33,46,47], which is consistent with the results of our study. In zebrafish, morpholino-mediated knockdown of mab21l2 resulted in microphthalmia and incomplete retinal development including discontinuous inner and outer plexiform layers [47].…”
Section: Discussionsupporting
confidence: 86%
“…Hyaloid vessels in mab21l2 morphants were also reported to be thicker and poorly patterned at 5dpf (Alvarez et al, 2007). These phenotypes are different than those observed in mab21l2 au10 mutants, and could reflect maternal compensation in the mutants, or compensation from mab21l1 , whose expression overlaps that of mab21l2 in many regions of the embryo, including the retina (Cederlund et al, 2011). Despite truncating the protein by roughly two-thirds, the mab21l2 au10 mutation could also be hypomorphic, and the truncated protein retains some of its endogenous function.…”
Section: Discussionmentioning
confidence: 80%
“…Mab21l2 expression has been observed in the optic vesicle of mice (Wong et al, 1999), Xenopus (Baldessari et al, 2004) and zebrafish (Wong and Chow, 2002), and it is detected in human retinal extracts (Margolis et al, 1996). In zebrafish, mab21l1 and mab21l2 are both expressed in the developing optic cup at 11hpf, with mab21l1 becoming enriched in the retina at 24hpf, and mab21l2 expressed in the lens and dorsal and nasal aspects of the retina (Cederlund et al, 2011). These published data are consistent with the hypothesis that au 10 possesses a mutation in mab21l2 , and to validate this, mRNA rescue was performed.…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear whether this cell is a newly identified amacrine subtype in zebrafish. Whereas the Ptf1A-driven GFP transgene did not identify this cell type (Jusuf and Harris 2009), the unique transgenic strain Tg(7.2mab21l2:EGFP)ucd2 did express GFP in a cell classified as a Type I ON cell that could be the same (Cederlund et al 2011). A direct comparison will be necessary to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…These studies, done in both zebrafish and mammalian systems, use stable transgenic lines and evaluate overlap between antibody staining and transgenic reporter expression (Sarthy et al 2007, Jusuf and Harris 2009, Cederlund et al 2011). There is not a stable transgenic zebrafish line expressing Tg(celsr3:EGFP) and in mosaic animals these studies are of little utility.…”
Section: Discussionmentioning
confidence: 99%